First observation of the Λ b 0 $$ Λ_b^0 $$ → D + D − Λ decay - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; J. A. Adams; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; et al. (Journal of High Energy Physics)
Abstract The Λ b 0 $$ Λ_b^0 $$ → D + D − Λ decay is observed for the first time using proton-proton collision data collected by the LHCb experiment at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.3 fb −1. Using the B 0 → D + D − K S 0 $$ D^{+}{D}^{-}{K}_S^0 $$ decay as a reference channel, the product of the relative production cross-section and decay branching fractions is measured to be R = σ Λ b 0 σ B 0 = B Λ b 0 → D + D − Λ B B 0 → D + D − K S 0 = 0.179 ± 0.022 ± 0.014 , $$ \mathcal{R}=\frac{σ_{Λ_b^0}}{σ_{B^0}}=\frac{\mathcal{B}\left(Λ_b^0→ D^{+}{D}^{-}Λ \right)}{\mathcal{B}\left(B^0→ D^{+}{D}^{-}{K}_{S}^0\right)}=0.179± 0.022± 0.014, $$ where the first uncertainty is statistical and the second is systematic. The known branching fraction of the reference channel, B B 0 → D + D − K S 0 $$ \mathcal{B}\left(B^0→ D^{+}{D}^{-}{K}_{S}^0\right) $$ , and the cross-section ratio, σ Λ b 0 / σ B 0 $$ σ_{Λ_b^0}/σ_{B^0} $$ , previously measured by LHCb are used to derive the branching fraction of the Λ b 0 $$ Λ_b^0 $$ → D + D − Λ decay B Λ b 0 → D + D − Λ = 1.24 ± 0.15 ± 0.10 ± 0.28 ± 0.11 × 10 − 4 , $$ \mathcal{B}\left(Λ_b^0→ D^{+}{D}^{-}Λ \right)=\left(1.24± 0.15± 0.10± 0.28± 0.11\right)× {10}^{-4}, $$ where the third and fourth contributions are due to uncertainties of B B 0 → D + D − K S 0 $$ \mathcal{B}\left(B^0→ D^{+}{D}^{-}{K}_{S}^0\right) $$ and σ Λ b 0 / σ B 0 $$ σ_{Λ_b^0}/σ_{B^0} $$ , respectively. Inspection of the D +Λ and D + D − invariant-mass distributions suggests a rich presence of intermediate resonances in the decay. The Λ b 0 $$ Λ_b^0 $$ → D *+ D − Λ decay is also observed for the first time as a partially reconstructed component in the D + D − Λ invariant mass spectrum.